Using the canva platform for english vocabulary reinforcement - Armijos Villavicencio, Denisse Brigeth; Cornejo Borbor, Daniela Stephanie (Machala : Universidad Técnica de Machala, 2021)
The present research aims to reinforce English vocabulary through a didactic activities system implementing the Canva platform as a didactic resource in third-year students of Elementary Basic General Education "A" of the School of Basic Education Manuel Encalada Zúñiga. This research responds to a paradigm qualitative, with a non-experimental design, from an action research participatory. To effectively develop the research, two methods were used essential, which are: Theoretical methods, in these are the historical-logical, inductive-deductive, analytical-synthetic and systemic, which enable to substantiate and demonstrate theoretically each aspect of the research, the empirical methods, where the participant observation, semi-structured interview and diagnostic test, which helped to identify the shortcomings that the population presented. Once the problem has been highlighted, executed the pedagogical proposal, where a system of didactic activities was implemented through tutorials, allowing students to interact more actively during the teaching-learning process of English vocabulary. Results were finally obtained favorable of this proposal through the assessment of effectiveness between the diagnostic test initial and final knowledge test.
La presente investigación tiene como objetivo es reforzar el vocabulario de inglés a través un sistema de actividades didácticas implementando la plataforma Canva como un recurso didáctico en los estudiantes de tercer año de Educación General Básica Elemental "A" de la Escuela de Educación Básica Manuel Encalada Zúñiga. Esta investigación responde a un paradigma cualitativo, con un diseño de carácter no experimental, desde una investigación-acción participativa. Para desarrollar de manera efectiva la investigación, se utilizó dos métodos esenciales, los cuales son: Métodos teóricos, en estos se encuentran el histórico-lógico, inductivo-deductivo, analítico-sintético y sistémico, los que permiten fundamentar y evidenciar de manera teórica cada aspecto de la investigación, los métodos empíricos, donde se utilizó la observación participante, entrevista semiestructurada y test diagnóstico, las cuales ayudaron a identificar las falencias que presentaba la población. Una vez evidenciada la problemática, se ejecutó la propuesta pedagógica, en donde se implementó un sistema de actividades didácticas por medio de tutorías, permitiendo que los estudiantes interactúen de manera más activa durante el proceso de enseñanza-aprendizaje del vocabulario de inglés. Finalmente se obtuvo resultados favorables de esta propuesta a través de la valorización de efectividad entre el test diagnóstico inicial y la prueba de conocimiento final.
Keywords: VOCABULARY; TEACHING RESOURCE; CANVA